(untitled) (Medical Forum Monthly, 2024)
Objective: There are limited cardiac centers dealing with paediatric cardiac surgery with enormous patient burden resulting long waiting lists due to manpower as well logistic issue . Therefore the concept of fast tracking is very attractive to overcome logistic issue. We describe our experience of postoperative fast-track extubation of children undergoing cardiac surgery. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the National Institute of Cardiovascular Diseases, Karachi from July 2015 to December 2015. Materials and Methods: Total 244 pediatric patients of less than 16 years of age were underwent definitive as well as palliative surgical intervention for congenital heart defects at National institute of cardiovascular diseases Karachi. Both male and female patients aged less than 15 years undergoing elective surgical procedures for Congenital heart defects or acquired heart effects on cardiopulmonary bypass (CPB) or off pump were included in the study. Patients with missing data like extubation time and whose were planned for overnight ventilation due to preoperative diagnosis or delayed due to surgical causes like mediastinal bleed were excluded from study Results: Among these patients fast tract extubation was observed in170(70%) and 74(30%) patients were extubated beyond 6 hours . While patient operated with the support of heart lung machine had higher number of delayed extubation rate that is 58(78.%) than off pump patients 16 (22%) p<.05 . Extubation failure was observed in 9 patients with 5 patient who were extubated on table (fast tract group ) and four patients extubated beyond six hours .(delayed extubation group). Conclusion: Fast tract extubation is successful in majority of patients operated for congenital heart defects. Early extubation is safe and is associated with reduction in length of ICU stay and better PCICU bed management without any effects on mortality or morbidity of patients after paeditaric cardiac surgery. It requires only desire for proactive management and team work without any specific protocol or algorithm to achieve early extubation.